TRANSFORMASI PENDIDIKAN PESANTREN MENUJU MODEL PENDIDIKAN ISLAM INKLUSIF DALAM MEWUJUDKAN EKOSISTEM MULTIKULTURAL SANTRI - Jazilurrahman; Miftahus Salam (Journal Multicultural of Islamic Education, 2026)
This study aims to describe and analyze in depth the Transformation of Islamic boarding school education towards an inclusive Islamic education model in realizing a multicultural ecosystem of students at the Nurul Jadid Paiton Probolinggo Islamic boarding school. In order to obtain data from the research results, a study was conducted with a qualitative approach and a type of ethnographic case study. This research was conducted at the Nurul Jadid Islamic boarding school, which is located in Karanganyar Village, Paiton District, Probolinggo Regency. This research was conducted from January to March 2026. The data collection technique used the snawball sampling technique. The data sources used were primary and secondary. Data collection techniques with participant observation, in-depth interviews and documentation. While the data analysis technique used the Spradley model with four types of analysis, namely domain analysis, taxonomic analysis, component analysis, and theme analysis. The results of this study indicate that the transformation of Islamic boarding school education towards an inclusive Islamic education model in realizing a multicultural ecosystem for students at the Nurul Jadid Paiton Probolinggo Islamic boarding school is the role model of inclusive exemplary Kiai, construction of inclusive Islamic education policies, development of an integrative and adaptive inclusive Islamic education curriculum, integration of inclusive values ​​in the learning process at school and internalization of inclusive values ​​through Islamic boarding school religious and social practices.